Rice Crop Current Developments - Shah, Farooq; Hayat Khan, Zafar; Iqbal, Amjad (IntechOpen, 2018)
Rice is a staple crop in many coastal and non-coastal areas of the globe and requires a large production area. With the increasing trends in population , it is pivotal to increase the production of this important crop for sustainability. The introduction of high-yielding rice cultivars through molecular breeding is one of the possibilities that can ensure sustainability. Additionally, development of new biotic and abiotic stress-resistant cultivars with higher nutritional value can revolutionize the rice industry.